Contributions of a Rehabilitation Nursing Program in the Self-Care of Women Undergoing Breast Surgery - Tânia Rodrigues; Maria Teresa Moreira; Andreia Lima; Rita Fernandes; Bárbara Gomes (MDPI AG, 2023)
Background: Although surgical treatments for breast cancer have exhibited advanced interventions, axillary lymph node dissection can limit functionality and compromise women's self-care. This study aims to assess the effectiveness of a rehabilitation nursing program in improving self-care performance in women undergoing breast surgery with axillary lymph node dissection. Methods: This quantitative, quasi-experimental study involved 48 women recruited from a main hospital between 2018 and 2019. The participants completed a three-month rehabilitation program at home. The evaluation instrument used was the DASH questionnaire. This study was not registered. Results: The functionality of the upper limb ipsilateral to the surgery improved significantly (p < 0.001) after the implementation of the program, influencing the participants' capacity for self-care, including washing/drying their hair, washing their back, and wearing a shirt. The average DASH total score increased from 54.4 to 8.1 after the program. Conclusions: The rehabilitation nursing program positively influenced the participants' self-care ability. Incorporating rehabilitation nursing programs into breast cancer treatment can improve self-care performance and the overall quality of patients' lives. This study was not registered.